2022
DOI: 10.1002/aelm.202101370
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Graphene Contacts and Passivation Layer for MoS2 Field Effect Transistors

Abstract: 2D materials have been considered as promising candidates for next-generation electronics since they offer unprecedented capability in device performance at the atomic limit through synergistic combination with silicon technology. [1,2] In particular, atomically thin 2D semiconductors, such as transition metal dichalcogenides (TMDs), have a desirable range of bandgap energies in the range between 1.0 and 2.5 eV and high carrier mobility up to 200 cm 2 V −1 s −1 , [3][4][5][6] thereby allowing integration into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Additionally, we have further confirmed that GaTe is identified as a p-type semiconductor from the Hall measurements. The carrier concentration decreases with the increase of temperature, and the carrier mobility increases with temperature, which is close to 100 cm 2 V –1 s –1 at room temperature, , demonstrating that T-GaTe is suitable for the preparation of high-performance devices. The temperature-dependent carrier concentration and mobility are contrary to the expected behavior of ordinary semiconductors, possibly because the opposite-type carrier is also generated over the measured temperature range, with a concentration greater than the increment of the dominant carrier, and the overall transport could be dominated by a ballistic nature .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we have further confirmed that GaTe is identified as a p-type semiconductor from the Hall measurements. The carrier concentration decreases with the increase of temperature, and the carrier mobility increases with temperature, which is close to 100 cm 2 V –1 s –1 at room temperature, , demonstrating that T-GaTe is suitable for the preparation of high-performance devices. The temperature-dependent carrier concentration and mobility are contrary to the expected behavior of ordinary semiconductors, possibly because the opposite-type carrier is also generated over the measured temperature range, with a concentration greater than the increment of the dominant carrier, and the overall transport could be dominated by a ballistic nature .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, semi-metallic contacts such as bismuth, antimony, and graphene have shown promising results [ 37 , 38 , 39 ]. However, semi-metal depositions involve heating of the substrate up to 100 °C to achieve a particular orientation of the metal (Sb 011 on ), which tends to introduce defects into heat-sensitive 2D semiconductors with ambipolar functionality, such as [ 40 , 41 ] and black phosphorus [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous XeF 2 vapor etching of 2D TMDs has also been explored for layer thinning and device fabrication when combined with nanolithography. , Conveniently, graphene is not spontaneously etched in XeF 2 , so it is an adequate etch stop for MoS 2 . Interestingly, fluorination of graphene causes sp 3 -type defects, as evidenced in the Raman D peak increase, which reduces the conductivity, whereas fully fluorine-passivated graphene is insulating. , …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, fluorination of graphene causes sp 3 -type defects, as evidenced in the Raman D peak increase, which reduces the conductivity, whereas fully fluorinepassivated graphene is insulating. 41,42 Here, we systematically explore FEBIE of MoS 2 mediated by an XeF 2 precursor. As our local pressures are much lower than previous spontaneous etching studies, negligible spontaneous etching is observed in what is presented, and we attribute the etching to synergistic electron-XeF 2 precursor interactions with the MoS 2 .…”
Section: ■ Introductionmentioning
confidence: 99%